1994
DOI: 10.1046/j.1365-313x.1994.05020157.x
|View full text |Cite
|
Sign up to set email alerts
|

Extensin: repetitive motifs, functional sites, post‐translational codes, and phylogeny

Abstract: Homologous hydroxyproline-rich glycoproteins (HRGPs) of the plant extracellular matrix include extensins, repetitive proline-rich proteins (RPRPs), some nodulins, gum arabic glycoprotein (GAGP), arabinogalactan-proteins (AGPs), and chimeric proteins such as potato lectin which contain an extensin module fused to a lectin. The key to the role of HRGPs in cell wall self-assembly and cell extension lies in their chemistry, which is dependent on extensive post-translational modifications (PTMs): hydroxylation, gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
432
1
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(448 citation statements)
references
References 0 publications
13
432
1
2
Order By: Relevance
“…In their proposal for a single, but diverse, H R G P superfamily, Kieliszewski and Lamport [25] described some examples of small functional peptide domains that are frequently found as repeating motifs, often within the context of larger repeat units. These include: (X)HypHyp(Hyp)n and ProProValTyrLys, which impart rigidity and an extended conformation to the molecule; ValTyrLys, TyrLysTyrLys and TyrTyrTyrLys, which are potential sites for inter-and intramolecular isodityrosine crosslinking; and finally, hydroxyproline, serine and threonine, all hydroxyamino acids that can serve as sites for O-linked glycosylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their proposal for a single, but diverse, H R G P superfamily, Kieliszewski and Lamport [25] described some examples of small functional peptide domains that are frequently found as repeating motifs, often within the context of larger repeat units. These include: (X)HypHyp(Hyp)n and ProProValTyrLys, which impart rigidity and an extended conformation to the molecule; ValTyrLys, TyrLysTyrLys and TyrTyrTyrLys, which are potential sites for inter-and intramolecular isodityrosine crosslinking; and finally, hydroxyproline, serine and threonine, all hydroxyamino acids that can serve as sites for O-linked glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the number of characterized HRGPs has increased, considerable variation has been found in the canonical repeats, and there has been a growing tendency to emphasize the novelty of these variants (e.g., monocot vs. dicot extensins). Recently, Kieliszewski and Lamport [25] suggested that we instead focus on the similarity of the HRGPs because they appear to belong to a common superfamily. If this is the case, it should be possible to trace the evolutionary origin of all HRGPs to a small number of archetypal peptide domains.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for galactosyl-O-Hyp, galactosyl-OSer, and arabinosyl-O-Hyp and unidentified glycosyl residues linked to Thr are reported for several AGPs [29]. Based on the Hyp-contiguity hypothesis, which briefly states that contiguous Hyp residues are glycosylated with oligoarabinosides, whereas single noncontiguous Hyp residues are glycosylated with polysaccharide units, glycosylation patterns can be predicted for AGP core protein sequences [31]. In other words, for AGPs, isolated Hyp residues appearing in the core protein are predicted to be the points of attachment of polysaccharide chains, whereas clusters of Hyp residues are predicted to be the potential sites of attachment for oligoarabinoside chains approximately four to six residues in length.…”
Section: Carbohydrate-core Protein Linkagesmentioning
confidence: 99%
“…Domain I1 consists of a 109 amino acid copper-binding domain. Domain 111 is a 26 amino acid peptide with hydroxyproline-and serine-rich repetitive sequence motifs characteristic of the hydroxyproline-rich proteins of the extensin family, extracellular structural glycoproteins found in plant cell walls (Showalter, 1993;Kieliszewski & Lamport, 1994). The C-terminal residue of the mature protein, SerI3', is followed by domain IV, an additional GAATTCGCGGCCGC TTTTTTACAACATCCTCATCCATG GCC GCC GGA TCA GTT GCC TTT 45 adaptor M A A G S V A F ACG GTT CAT ATC GTC GGC GAC PAC ACC GGT TGG AGT GTT CCA TCG AGC CCC 147 T V H I V G D N T G W S V P S S P 10 AAT TTC TAT TCT CAA TGG GCT GCT GGA M G ACC TTC CGC GTT GGC GAT TCT 198 N F Y S Q W A A G K T F R V G D S 20 30 CTC CAA TTT AAC TTT CCA GCC RAT GCC CAC M C GTA CAT GAA ATG GAA ACA 249 L Q F N F P A N A H N V H E M E T 40 50 AAA CAG TCG TTT GAT GCA TGT RAT TTT GTC AAT TCT GAT AAC GAT GTC GAG 300 K Q S F D A C N F V N S D N D V E 60 70 AGG ACA TCT CCA GTG ATA GAG AGA CTC GAC GAA CTC GGC ATG CAT TAC TTT 351 R T S P V I E R L D E L G M H Y F 80 GTT TGC ACC GTT GGA ACA CAT TGT TCA AAT GGT CAR AAG TTA TCC 22-amino acid hydrophobic polypeptide extension.…”
Section: Isolation Of Cdnas Encoding C Sativus Stellacyanin and Exprmentioning
confidence: 99%